Communicative Language Preferences in Gen Xs, Millennials and Gen Zs for Workplace Communication - Jefry, Basyirah (Association of Language Teachers in Southeast Asia (ALTSA), 2024)
This study examined how Generation X (born 1965–1980), Millennials (born 1981–1996), and Generation Z (born 1997–2012) adapt to formal and informal communication in Brunei’s government sector. It was based on Communication Accommodation Theory and Social Identity Theory. These frameworks helped explain how different generations adjust their communication styles. The study used a descriptive survey method. Researchers collected responses from 60 participants working in various government ministries. The findings show that Gen Z and Millennials are more comfortable using messaging apps like WhatsApp for faster daily communication. Gen X still prefers email, memos, and face-to-face conversations, especially for formal purposes. Although technology is already common in many offices, formal communication remains important. This is due to Brunei’s working culture and the influence of Melayu Islam Beraja (MIB). Some Gen Z respondents felt uncertain when speaking with their senior Gen X colleagues. Gen X often finds informal messaging a bit unprofessional. Millennials, on the other hand, are more flexible and can switch between styles depending on who they are communicating with. This study suggests that better intergenerational communication can be achieved by encouraging mentorship between older and younger workers. Offering training for digital communication and building a respectful environment that supports both traditional and modern practices are also beneficial. Overall, the research indicates that combining cultural values with effective communication adaptation is crucial. This helps maintain harmony and productivity in Brunei’s multigenerational government workplaces.